Neonatal bleeding disorders. A practical diagnostic approach - Georgios N. Katsaras; Dimitra Gialamprinou; Euthimia Papacharalampous; Ilias Chatziioannidis; Georgios Mitsiakos (Journal of Pediatric and Neonatal Individualized Medicine, 2022)
Since developmental hemostasis was introduced by Andrew et al. in the early 90s, age-related variations in coagulation components have been a well-established knowledge. In parallel with age-dependent hemostatic status maturation, coagulation disorders assessment stands as an important prerequisite for bleeding management. However, discrepancies observed between neonatal coagulation reference ranges and standard coagulation assays extrapolated from adults make neonatal disease evaluation and therapeutic management challenging. This study aims to provide a diagnostic approach to neonatal bleeding based on a current literature search on bleeding disorders in the neonatal period.